Implementasi Algoritme BLAKE2b untuk Pengecekan Integritas File - Pramasita Gustiarum; Ari Kusyanti; Mahendra Data (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
File is an object on a computer that stores data and information that can be read by a program on a computer. On computers, files are stored in storage, such as hard drives, DVDs, flash disks and so on. Other than being stored, files can also be moved, shared, changed and duplicated. From these processes, protecting file integrity is very important because these processes can affect data or information stored in it. Possibility of threats in that processes might be corrupted data, data unwantedly modify or file carries hidden data for criminal purposes. Therefore, there is need for a mechanism to check integrity of the data using cryptographic techniques, called hashing. Hashing is a technique to generate unique values from a string and this unique what we called hash value or digest. In this study, BLAKE2b hash function is used as data integrity validation of a file. The experiment in this study includes, timing BLAKE2b to validate .txt file format, which given result of average 18.60s for 500 KB file in size. Next results of BLAKE2b process time are compared with MD5 and the results obtained in this experiment are average of 15.85s and 18.30s for each algorithm, it can be concluded that BLAKE2b is working slightly faster than MD5. Lastly, avalanche test of BLAKE2b gives an average probability of 0.589.